Electrically bioactive coating on Ti with bi-layered SnO2–TiO2 hetero-structure for improving osteointegration. Issue 23 (4th June 2018) - Zhou, Rui; Han, Yong; Cao, Jianyun; Li, Ming; Jin, Guorui; Luo, Haoteng; Zhang, Lizhai; Su, Bo
Abstract : SnO2 –TiO2 surface with the bi-layered structure on Ti provides internal electric stimulation to promote osteointegration of implant. Abstract : The potential for the use of electric stimulation to control cell behavior on a surface has been well documented. In terms of orthopaedic applications, there is a need to develop bioactive surfaces with a built-in electric field for clinically relevant materials, such as load-bearing titanium (Ti). In this work, a bi-layered SnO2 –TiO2 coating is fabricated via microarc oxidation and subsequent hydrothermal treatment to adjust the surface electrical properties for improving bioactivity. An oxidized titanium interlayer on Ti substrate allows the growth of SnO2 nanorods with different morphologies, which leads to a built-in n–n heterojunction of SnO2 and TiO2 on the Ti surface with varied surface electrical properties. The crystallization of the TiO2 interlayer facilitates the growth of SnO2 nanorods, showing excellent hydrophilicity and good apatite-inducing ability due to the formation of a heterojunction. The results suggest that the bi-layered SnO2 –TiO2 coating with electrically stimulated bioactivity could provide a novel way to enhance osteointegration on the Ti surface.